(untitled) - Dacey, John S. (San Francisco, CA, 2006)
The Safe Child Handbook is a practical guide for protecting your family in a way that reduces the stress that can so often sabotage such well-intentioned efforts. Step-by-step, the book shows how to prepare and protect your family from realistic threats and, at the same time, alleviate fearfulness and anxiety in you and your children. The Safe Child Handbook outlines the top eight threats to children and parents—weather emergencies, kidnapping, terrorism, inappropriate media influence, drug and alcohol abuse, child abuse, school violence, and home safety—and shows how to be ready to face the most drastic situations with confidence. The Safe Child Handbook is filled with practical advice, activities for children, and techniques that will empower your whole family.
Keywords: Safety education,Child rearing,Children’s accidents,Giáo dục an toàn,Con nuôi,Tai nạn của trẻ nhỏ; Prevention,Ngăn ngừa; United States,United States,United States,Hoa Kỳ,Hoa Kỳ,Hoa Kỳ